Synthesis and Crystal Structure of 1,4-Bis(2-methylphenyl)-2,5-piperazinedione - Wen, Yong-Hong; Zhang , Shu-Sheng; Yu, Bao-Hui; Li, Xue-Mei; Lui, Qing (Asian Journal of Chemistry, 2010)
The crystal structure of 1,4-bis(2-methylphenyl)-2,5-piperazinedione has been determined by single crystal X-ray diffraction method. The crystal belongs to monoclinic system, space group P-1 with unit cell constants a = 10.372 (3), b = 12.224 (3), c = 12.614 (3) Å, α = 95.448 (4), β = 101.751 (4), γ = 90.072 (5), V = 1558.4 (7) Å3, Z = 2, Dc = 1.255 g/cm–3, μ = 0.083 mm–1, F(000) = 624, R and wR are 0.0707 and 0.2067, respectively for 5990 unique reflections with 3580 observed reflections [I >2 σ(I)]. The title compound, C18H18N2O2, (I), contains two independent molecules in the asymmetric unit. The dihedral angles between the two benzene rings in each molecule are 3.7 (2) and 3.2 (2)º. Molecules of (I) interact via weak intermolecular C––H...O interactions, forming zig-zag chains along the a-axis.